(untitled) (Bangladesh Journal of Medicine, 2021)
Hanging is one of the common forms of violent mechanical asphyxial death. When compared to other forms of unnatural death all over the world this method stands on top as death is instantaneous.Hanging is always suicidal unless otherwise proved. The aim of this study is to gain new knowledge that would enable the design of effective of measures that would help to prevent suicide by hanging. In this case report, we will discuss the unusual presentation of a young lady who attempts suicide frequently did not result in death. We present data indicating that victims can be resuscitated even after prolonged period of suspension & unconsciousness & some of the reasons why asphyxiation by hanging may be delayed when there is no damage to the spinal cord. The logical, thoughtful management options that we chose at various stages of her disease in general ward with the use of colistin which eventually led to her cure are also discussed here. Emphasis is given on how these tricky cases can be deal with prognostically good results could be achieved, if such victims are vigorously & promptly resuscitated, irrespective of her initial presentation. Bangladesh J Medicine January 2021; 32(1) : 53-57